The young protostellar disc in IRAS 16293−2422 B is hot and shows signatures of gravitational instability. Issue 2 (20th September 2021) - Zamponi, Joaquin; Maureira, María José; Zhao, Bo; Liu, Hauyu Baobab; Ilee, John D; Forgan, Duncan; Caselli, Paola
ABSTRACT: Deeply embedded protostars are actively fed from their surrounding envelopes through their protostellar disc. The physical structure of such early discs might be different from that of more evolved sources due to the active accretion. We present 1.3 and 3 mm ALMA continuum observations at resolutions of 6.5 and 12 au, respectively, towards the Class 0 source IRAS 16293−2422 B. The resolved brightness temperatures appear remarkably high, with T b > 100 K within ∼30 au and T b peak over 400 K at 3 mm. Both wavelengths show a lopsided emission with a spectral index reaching values less than 2 in the central ∼20 au region. We compare these observations with a series of radiative transfer calculations and synthetic observations of magnetohydrodynamic and radiation hydrodynamic protostellar disc models formed after the collapse of a dense core. Based on our results, we argue that the gas kinematics within the disc may play a more significant role in heating the disc than the protostellar radiation. In particular, our radiation hydrodynamic simulation of disc formation, including heating sources associated with gravitational instabilities, is able to generate the temperatures necessary to explain the high fluxes observed in IRAS 16293B. Besides, the low spectral index values are naturally reproduced by the high optical depth and high inner temperatures of the protostellar disc models. The high temperatures in IRAS 16293B imply that volatile species are mostly in the gas phase, suggesting that a self-gravitating disc could be at the origin of a hot corino.